Timing of First Milk Expression to Maximize Breastfeeding Continuation Among Mothers of Very Low-Birth-Weight Infants. Issue 6 (June 2019) - Parker, Margaret G.; Melvin, Patrice; Graham, Dionne A.; Gupta, Munish; Burnham, Laura A.; Lopera, Adriana M.; Zera, Chloe A.; Belfort, Mandy B.
Abstract : OBJECTIVE: To estimate the time of first milk expression among mothers of very low-birth-weight (VLBW, 1, 500 g or less) infants that predicts the maximal duration of mother's milk provision during hospitalization in the neonatal intensive care unit (NICU). METHODS: We performed a secondary analysis and studied 1, 157 mother–VLBW infant pairs in nine Massachusetts hospitals born from January 2015 until December 2017. We determined the cut-point for timing of first milk expression after delivery that was associated with the highest probability of any and exclusive provision of mother's milk for the infant at NICU discharge or transfer using recursive partitioning. We estimated hazard ratios (HRs) comparing the probability of continued provision of mother's milk during the hospitalization between mothers who initiated milk expression before compared with after the cut-point (within 8 hours after delivery [referent] vs 9–24 hours), adjusting for gestational age, birth weight, maternal race and ethnicity, and clustering by hospital and plurality in Cox proportional hazards models. RESULTS: Sixty-eight percent of mothers first expressed milk within 8 hours after delivery. First milk expression at 9–24 hours was associated with lower odds of any mother's milk provided to the infant on day 7 (adjusted odds ratio [aOR] 0.39 [0.24–0.60]) and discharge or transfer (aOR 0.45 [0.33–0.62]), compared with expression within 8 hours. Findings were similar for exclusive mother's milk. Mothers who first expressed 9–24 hours stopped providing milk earlier in the neonatal hospitalization (adjusted HR 1.64 [1.33–2.01]) compared with mothers who first expressed within 8 hours. CONCLUSION: Using a data-driven approach, we identified that first milk expression within 8 hours was superior to 9–24 hours with respect to maximal duration of provision of mother's milk for hospitalized VLBW infants. Randomized control trials are needed to further establish the causal relationship between timing of first milk expression and long-term lactation success among mothers of VLBW infants. Abstract : First milk expression within 8 hours after delivery was superior to 9–24 hours with respect to maximal duration of mother's milk provision for very low-birth-weight infants.